2016
DOI: 10.1038/srep27866
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Induces Apoptosis in Cultured Neonatal Rat Cardiomyocytes by Modulating the TLR4/NF-κB Pathway

Abstract: This study was designed to investigate the apoptosis induced by oxidized low-density lipoprotein (ox-LDL) in cultured neonatal rat cardiomyocytes and explore the possible mechanisms. We evaluated whether ox-LDL-induced apoptosis depended in part on the activation of toll-like receptor-4(TLR4)/Nuclear factor κB (NF-κB) signaling pathway. Cells were cultivated with and without ox-LDL. Cell apoptosis was evaluated by flow cytometry. Immunofluorescence, western blot analysis and quantitative real-time polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Recent studies have suggested that EGFR can also be activated without the typical ligands29, and it can function in intracellular membranes30. Toll-like receptor 4 (TLR4) has been reported to be directly activated by ox-LDL and mediate pathological pathways and phenotypes313233. In addition, expression of TLR4-induced genes in lipopolysaccharide-stimulated myeloid cells requires EGFR kinase activity18.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that EGFR can also be activated without the typical ligands29, and it can function in intracellular membranes30. Toll-like receptor 4 (TLR4) has been reported to be directly activated by ox-LDL and mediate pathological pathways and phenotypes313233. In addition, expression of TLR4-induced genes in lipopolysaccharide-stimulated myeloid cells requires EGFR kinase activity18.…”
Section: Resultsmentioning
confidence: 99%
“…2 Ox-LDL induces oxida-tive stress by activating reactive oxygen species (ROS), malondialdehyde (MDA), and superoxide dismutase (SOD), releasing proinflammatory cytokines and modulating the activity of antioxidant enzymes. 6,7 Normally, excessive or increased ox-LDL would be captured by macrophages via scavenger receptors, such as CD36, 8 which ultimately triggers metabolic disorders and macrophage apoptosis. 6,7 Normally, excessive or increased ox-LDL would be captured by macrophages via scavenger receptors, such as CD36, 8 which ultimately triggers metabolic disorders and macrophage apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Emerging studies have demonstrated that ox-LDL also plays pivotal roles in apoptosis, a process of programmed cell death that is closely associated with atherogenesis and other disorders. 6,7 Normally, excessive or increased ox-LDL would be captured by macrophages via scavenger receptors, such as CD36, 8 which ultimately triggers metabolic disorders and macrophage apoptosis. 9 Reducing the oxidative stress by antioxidant or thiol reductant treatment, or overexpression of thioredoxin or manganese superoxide could largely ameliorate apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor‐kappa B (NF‐κB) is a transcription factor that contains five members, namely, NF‐κB 1(p50/p105), NF‐κB 2(p52/p100), RelA(p65), RelB, and c‐Rel, controlling the expression of genes involved in cell cycle, immune responses, cell and tissue differentiation, and DNA repair (Panday et al, ). RelA has long been regarded as oncogenic in many solid cancers and hematologic malignancies (Y. J. Chen et al, ; W. Chen, Li, Bai, & Lin, ); however, some reports have also shown RelA to act as a biphasic regulator or even to demonstrate antitumor capabilities (Chien et al, ; Yang et al, ) and the activation of TLR4/NF‐κB signaling pathway trigger the apoptotic cascades (X. Wang, Sun, Yang, Lu, & Li, ). Our research demonstrated that AP could not decrease the percentage of MDSCs in splenocytes of TLR4 knockout mice with colon tumor, and in wild type MDSCs, RelA was phosphorylated after the cells were exposed to AP (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen, Li, Bai, & Lin, 2011); however, some reports have also shown RelA to act as a biphasic regulator or even to demonstrate antitumor capabilities (Chien et al, 2011;Yang et al, 2011) and the activation of TLR4/NF-κB signaling pathway trigger the apoptotic cascades (X. Wang, Sun, Yang, Lu, & Li, 2016). Our research demonstrated that AP could not decrease the percentage of MDSCs in splenocytes of TLR4 knockout mice with colon tumor, and in wild type MDSCs, RelA was phosphorylated after the cells were exposed to AP ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%